2018
DOI: 10.1093/cvr/cvy018
|View full text |Cite
|
Sign up to set email alerts
|

Targeted endothelial gene deletion of triggering receptor expressed on myeloid cells-1 protects mice during septic shock

Abstract: We reported that TREM-1 is expressed and inducible in endothelial cells and plays a direct role in vascular inflammation and dysfunction. The targeted deletion of endothelial Trem-1 conferred protection during septic shock in modulating inflammatory cells mobilization and activation, restoring vasoreactivity, and improving survival. The effect of TREM-1 on vascular tone, while impressive, deserves further investigations including the design of endothelium-specific TREM-1 inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 32 publications
4
32
0
Order By: Relevance
“…TREM-1 blockade using the extracellular domain of TREM-1 fusion IgG or synthetic TREM-1 antagonistic peptide LP17 ameliorated the clinical manifestations of collagen-induced arthritis (CIA) [ 37 ]. In addition, pharmacological inhibition of TREM-1 using LR12, a synthetic inhibitory peptide, protected mice during septic shock in vitro and in vivo [ 38 ], and the LR12 peptide is now under clinical trials in septic patients ( www.clinicaltrials.gov , NCT03158948). Consistent with the previous studies, our results demonstrated that blockade of TREM-1 with LP17 significantly reduced the spontaneous secretion of IL-1β, IL-6 and IL-8 in the neutrophils of AOSD patients, indicating the involvement of TREM-1 in the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…TREM-1 blockade using the extracellular domain of TREM-1 fusion IgG or synthetic TREM-1 antagonistic peptide LP17 ameliorated the clinical manifestations of collagen-induced arthritis (CIA) [ 37 ]. In addition, pharmacological inhibition of TREM-1 using LR12, a synthetic inhibitory peptide, protected mice during septic shock in vitro and in vivo [ 38 ], and the LR12 peptide is now under clinical trials in septic patients ( www.clinicaltrials.gov , NCT03158948). Consistent with the previous studies, our results demonstrated that blockade of TREM-1 with LP17 significantly reduced the spontaneous secretion of IL-1β, IL-6 and IL-8 in the neutrophils of AOSD patients, indicating the involvement of TREM-1 in the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Leukocyte trafficking was analyzed by flow cytometry as previously described [33]. The spleen and liver were crushed in HBSS and filtered on a 70-μm nylon filter.…”
Section: Methodsmentioning
confidence: 99%
“…Myeloid cell trigger receptor-1 (TREM-1) is a member of the immunoglobulin super receptor family mainly expressed on the surface of myeloid cells such as neutrophils and monocytes/macrophages [16]. Soluble TREM-1 (sTREM-1), one of the two forms of TREM-1, has been reported as a novel and strong indicator of pneumonia [17].…”
Section: Introductionmentioning
confidence: 99%